Glycyrrhetinic Acid-Poly(ethylene glycol)-glycyrrhetinic Acid Tri-Block Conjugates Based Self-Assembled Micelles for Hepatic Targeted Delivery of Poorly Water Soluble Drug. (25th November 2013) - Wu, Fengbo; Xu, Ting; Liu, Chi; Chen, Can; Song, Xiangrong; Zheng, Yu; He, Gu
Abstract : The triblock 18 β -glycyrrhetinic acid-poly(ethylene glycol)-18 β -glycyrrhetinic acid conjugates (GA-PEG-GA) based self-assembled micelles were synthesized and characterized by FTIR, NMR, transmission electron microscopy, and particle size analysis. The GA-PEG-GA conjugates having the critical micelle concentration of 6 × 10 - 5 M were used to form nanosized micelles, with mean diameters of 159.21 ± 2.2 nm, and then paclitaxel (PTX) was incorporated into GA-PEG-GA micelles by self-assembly method. The physicochemical properties of the PTX loaded GA-PEG-GA micelles were evaluated including in vitro cellular uptake, cytotoxicity, drug release profile, and in vivo tissue distribution. The results demonstrate that the GA-PEG-GA micelles had low cytotoxicity and good ability of selectively delivering drug to hepatic cells in vitro and in vivo by the targeting moiety glycyrrhetinic acid. In conclusion, the GA-PEG-GA conjugates have potential medical applications for targeted delivery of poor soluble drug delivery.